Methyl-substituted cucurbit[6]uril-based microporous supramolecular frameworks for highly selective Et2O/CH3OH adsorption. Issue 12 (2nd March 2016) - Wang, Chuan-Zeng; Zhao, Wen-Xuan; Shen, Fang-Fang; Zhang, Yun-Qian; Zhu, Qian-Jiang; Xiao, Xin; Tao, Zhu
Abstract : Two kinds of microporous supramolecular frameworks of methyl-substituted cucurbit[6]uril (HMeQ[6]) derived from 3-α-methyl-glycoluril with Ca 2+ and Ba 2+ cations are formed in the presence of [CdCl4 ] 2− as a structure-directing agent. Abstract : The interaction and supramolecular assemblies of two alkaline earth metal ions, Ca 2+ and Ba 2+, with methyl-substituted cucurbit[6]uril derived from 3α-methyl-glycoluril (HMeQ[6]) in aqueous HCl solution have been investigated. X-ray diffraction analysis revealed that coordination of HMeQ[6] with these metal ions resulted in the formation of one-dimensional coordination polymers in the presence of polychloride transition metal anions, such as [CdCl4 ] 2−, as structure-directing agents. The supramolecular frameworks exhibit excellent thermal stability as well as permanent porosity. The activated desolvated materials show high Et2 O and CH3 OH adsorption capacity and selectivity compared with other porous organic materials assembled solely through hydrogen bonding under ambient conditions.